PERFORMANCE IMPROVEMENT STRATEGY OF AMBULAN HEBAT WITH THE PRINCIPLES OF SMART MOBILITY FOR EMERGENCY MEDICAL SERVICES IN SEMARANG CITY, MASTERâS THESIS, INSTITUT TEKNOLOGI BANDUNG - Septylia Choirotun Nisak, Nur
A smart city is considered an effort to strengthen the city's quality and solutions towards sustainability and resilience. One indicator of a city's resilience is accessibility from/to emergency services/hospitals. Ambulances as a form of urban resilience play an important role in supporting the resilience and readiness of cities to face various health crises and challenges and are also able to provide a quick and appropriate response during an accident, emergency incident, or disease outbreak. The Ambulan Hebat is an effort made by the Semarang City Government as an emergency service that requires quick follow-up services. In the implementation of the Ambulan Hebat, there are still many obstacles that have an impact on the performance of the Ambulan Hebat that became less optimal. The increasing population has an impact on increasing traffic volume which can slow down ambulance response time to the location of patients and referral hospitals. The facilities and infrastructures of the Ambulan Hebat are still very limited. There are still many areas that are difficult to reach by ambulance teams with limited ambulance instruments in accessing the fastest route. The system in the Ambulan Hebat has also not been automatically connected with hospitals, data centers, and traffic management to create better ambulance accessibility. Utilizing technological advances and the concept of smart mobility, it has opened an opportunity to improve the performance of ambulance services. The application of technologies such as navigation systems, real-time traffic monitoring, and connected ambulance systems can help optimize ambulance travel in overcoming traffic challenges that require response time as quickly as possible. To achieve this goal, the strategy of improving ambulance performance with the principle of smart mobility becomes a relevant and effective approach. This study uses statistical descriptive analysis to identify the performance characteristics of the Ambulan Hebat, both in terms of accessibility, key performance smart medical emergency vehicle, utilization of information and communication technology, and traffic conditions. The performance characteristics of the existing Ambulan Hebat will be presented in the narrative and pie chart to determine the level of disposition and achievement of the Ambulan Hebat. Meanwhile, the grouping of response time duration will be presented in tabular form to make it easier to understand the response time of the Ambulan Hebat and to make it easier to compare existing travel times based on the manual recording by operators and ideal travel times iv calculated by OSRM (Open-Sourced Routing Machine). To view the potential of the application of smart mobility principles in the Ambulan Hebat, it will be presented in a comparison table with the ideal conditions of smart ambulance that have been applied in several developed countries. Meanwhile, to see whether there is a relationship between the response time of the Ambulan Hebat and the level of traffic density, Pearson correlation analysis is used. To find out the challenges and obstacles in the implementation of the Ambulan Hebat, a qualitative analysis was made. The findings of the identification of ambulance characteristics and the identification of challenges and constraints, a synthesis of internal and external factors in the development of the Ambulan Hebat service was compiled, which was then made with the SWOT analysis to identify strategies to improve the performance of the Ambulan Hebat service in Semarang City. The formulation of the strategy results of the SWOT analysis is then grouped into short-term, medium-term, and long-term strategies.